R-Test Static Measurement of The 5-axis CNC Machining Centre Rotary Axis Kinematic Centre Error - Jozwik, Jerzy; Lonkwic, Pawel; Saga, Milan; Kuric, Ivan (Manufacturing Technology Journal, 2014)
This paper presents static measurements results of the kinematic pair centre of the C-rotary axis of the 5-axis machine tool at digitised angle positions αof the machine rotary table. The measurements were conducted with the application of R-test calibration and measuring system. The article discusses the test sequence as well as the evaluation of the kinematic centre location of the rotary axis, relative to linear X, Y-axis. The summary formulates guidelines covering the compensation of the axis location. Measurement results were presented in diagrams and tables.
Keywords: manufacturing; errors of CNC machine tool; diagnostic systems; calibration; R-test